“More than an intensive care phenomenon”: Religious communities and the WHO Guidelines for Ebola and Covid-19: „Mehr als ein Phänomen der Intensivpflege“: Religiöse Gemeinschaften und die WHO Richtlinien für Ebola und Covid-19 - Winiger, Fabian (Spiritual care, 2020)
This article draws on anthropological fieldwork conducted during the West African Ebola outbreak (2014-2016) and reports of the ongoing Covid-19 crisis to discuss the role played by religion in infectious disease control. While much separates Ebola and Covid-19, the religious practices prevalent in both contexts produce similar challenges to hospital staff and caregivers. In West Africa, at least 20 % of all infections were suspected to be related to the burial of deceased Ebola victims; yet at the same time, local communities at times reacted very negatively to infectious disease control measures. This article discusses how, based on this recognition, a systematic exchange began between anthropologists, faith-based organisations (FBOs) and humanitarian organisations active in the provision of healthcare, culminating in a WHO protocol for the “safe and dignified” burial of Ebola victims. The model of ‘contactless’ adaptations of religious practices it put forth may have significantly contributed to the control of the epidemic. In the second part, this article turns to the Covid-19 pandemic to show how religious communities have responded to the risks associated with many religious practices, and how the WHO, drawing on its experience with Ebola, developed comparable guidelines aimed at religious leaders and faith communities. As the experience in West Africa has shown, it is argued, the active involvement of religious actors in the formulation of public health measures may not only help to provide safe comfort in the midst of a profoundly alienating experience, but significantly reduce the spread of the virus.